Mating Disruption of Chilo suppressalis From Sex Pheromone of Another Pyralid Rice Pest Cnaphalocrocis medinalis (Lepidoptera: Pyralidae). Issue 3 (19th June 2020) - Liang, Yu-yong; Luo, Mei; Fu, Xiao-gang; Zheng, Li-xia; Wei, Hong-yi
Abstract: The rice stem borer, Chilo suppressalis (Walker), and the rice leaf folder, Cnaphalocrocis medinalis Guenée, are two of the most destructive lepidopteran pests in rice. Since these two pyralid insects overlap in their occurrence in rice paddy fields, farmers prefer to set their pheromone-baited traps together in the rice fields for their monitoring. However, our field observation demonstrated that no male adult of C. suppressalis was captured in traps baited with commercial sex pheromone of C. suppressalis (CCS) combined with commercial sex pheromone of C. medinalis (CCM). To confirm that the C. medinalis sex pheromone component(s) interfere with the attraction of males of the rice stem borers to their conspecific females, single components of C. medinalis sex pheromone combined with CCS in traps were tested in the laboratory and rice paddy field. The results revealed that the two alcohol components in CCM, i.e., ( Z )-11-octadecen-1-ol (Z11-18: OH) and ( Z )-13-octadecen-1-ol (Z13-18: OH) may cause a significant reduction in capturing C. suppressalis males caused by CCS. We recommend against using these sex pheromones together in the field and suggest that Z11-18: OH and Z13-18: OH could be potential inhibitors or antagonists of C. suppressalis sex pheromone to control the rice stem borer.